1984
DOI: 10.1136/jcp.37.7.796
|View full text |Cite
|
Sign up to set email alerts
|

Detection of toxin production by Corynebacterium diphtheriae: results of a trial organised as part of the United Kingdom National External Microbiological Quality Assessment Scheme.

Abstract: SUMMARY Four strains of Corynebacterium diphtheriae were sent to UK participants in the UK National External Microbiological Quality Assessment Scheme, who were asked to examine the strains for toxin production by in vitro methods. Laboratories achieved 162/176 (92%) and 160/175 (91 %) correct results with two rapid toxin producers and 145/175 (82%) with a slow toxin producer. With a non-toxigenic strain 26/175 (15%) laboratories reported toxin production. Of the 173 laboratories reporting on all four strains,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Discs were dried at 37ЊC for 1 h and used to determine the effect of antitoxin concentration on the detection of toxigenicity. Plates were inoculated at various distances (3,6,9,12, and 15 mm) from the edge of the antitoxin disc (10 IU/disc) with a light, medium, or heavy inoculum to determine the effects of density and distance of inocula on detection of toxigenicity.…”
Section: Development and Optimization Of The Modified Elek Test The mentioning
confidence: 99%
“…Discs were dried at 37ЊC for 1 h and used to determine the effect of antitoxin concentration on the detection of toxigenicity. Plates were inoculated at various distances (3,6,9,12, and 15 mm) from the edge of the antitoxin disc (10 IU/disc) with a light, medium, or heavy inoculum to determine the effects of density and distance of inocula on detection of toxigenicity.…”
Section: Development and Optimization Of The Modified Elek Test The mentioning
confidence: 99%
“…Even if the technique is standardized, the test is technically demanding and needs to be rigidly quality controlled. Furthermore, a microbiological quality assessment trial for examining toxin production by in vitro methods showed that only 69% of the laboratories achieved the correct result (23). The large amount of effort needed to ensure satisfactory results with the Elek test suggests the necessity of a simple and reliable in vitro method for DT detection.…”
mentioning
confidence: 99%
“…Currently, the only in vitro method readily available to the majority of diagnostic laboratories is the Elek immunoprecipitation test, first described in 1949, which is both technically demanding and prone to misinterpretation (2). Difficulties with the application of the Elek test have been reported (12): in a United Kingdom national external quality assessment scheme conducted in 1984, only 69% (120 of 173) of participating laboratories obtained the correct result for all four strains of C. diphtheriae distributed. Although the clarity and accuracy of the test have been improved following the modification of the Elek medium (1), the misinterpretation of nonspecific precipitin lines remains common, particularly in laboratories where the test is performed infrequently.…”
mentioning
confidence: 99%
“…Discs were dried at 37ЊC for 1 h and used to determine the effect of antitoxin concentration on the detection of toxigenicity. Plates were inoculated at various distances (3,6,9,12, and 15 mm) from the edge of the antitoxin disc (10 IU/disc) with a light, medium, or heavy inoculum to determine the effects of density and distance of inocula on detection of toxigenicity.…”
mentioning
confidence: 99%